Suppression of superconductivity and resistivity anomaly in Rh17S15 by cobalt substitution. (30th December 2016) - Daou, Ramzy; Berthebaud, David; Maignan, Antoine
Abstract: The chalcogenide superconductor Rh17 S15 is known for having an upper critical field of nearly twice the Pauli limit and an unusual temperature dependence of the resistivity. When doped with small amounts of cobalt, superconductivity in Rh17− x Co x S15 (0 < x < 3) is systematically suppressed. We explore the evolution of the electrical transport properties from 2–300 K as a function of x . We identify three temperature regimes which are differently affected by doping. The disappearance of an electron-like contribution to the transport at low temperature is correlated with the suppression of superconductivity.